WITHDRAWAL Monitoring of Caffeine Consumption Effect on Skin Blood Properties by Diffuse Reflectance Spectroscopy - Milanic, M; Hren, R; Stergar, J; Simoncic, U (Physiological research, 2025)
Matija MILANIC1,2, Rok HREN1,3,4, Jost STERGAR1,2, Urban SIMONCIC1,2 1Faculty of Mathematics and Physics, University of Ljubljana, Ljubljana, Republic of Slovenia, 2Jožef Stefan Institute, Ljubljana, Republic of Slovenia, 3Institute of Mathematics, Physics, and Mechanics, Ljubljana, Republic of Slovenia, 4Syreon Research Institute, Budapest, Hungary Physiol Res 2024 Mar 11;73(1):47-56. doi: 10.33549/physiolres.935138. PMID: 38466004 This paper has been retracted on the base of author ́s request.
Keywords: dospělí; Caffeine; mladý dospělý; lidé; kofein; spektrální analýza; mužské pohlaví; Female; Young Adult; Male; Skin; kůže; Spectrum Analysis; Adult; ženské pohlaví; Humans